LncRNAs in oncogenic microenvironment: from threat to therapy - Roy, Dipanjan; Bhattacharya, Bireswar; Chakravarti, Rudra; Singh, Prabhjot; Arya, Mansi; Kundu, Anirban; Patil, Ajay; Siva, Bhukiya; Mehta, Sunny; Kazi, Tawsif Ahmed; Ghosh, Dipanjan (Frontiers in Cell and Developmental Biology, 2025)
LncRNAs are RNA molecules of more than 200 nucleotides in length and participate in cellular metabolism and cellular responses through their diverse interactomedespite having no protein-coding capabilities. Such significant interactions also implicate the presence of lncRNAs in complex pathobiological pathways of various diseases, affecting cellular survival by modulating autophagy, inflammation and apoptosis. Proliferating cells harbour a complex microenvironment that mainly stimulate growth-specific activities such as DNA replication, repair, and protein synthesis. They also recognise damages at the macromolecular level, preventing them from reaching the next-generation. LncRNAs have shown significant association with the events occurring towards proliferation, regulating key events in dividing cells, and dysregulation of lncRNA transcriptome affects normal cellular life-cycle, promoting the development of cancer. Furthermore, lncRNAs also demonstrated an association with cancer growth and progression by regulating key pathways governing cell growth, epithelial-mesenchymal transition and metastasis. This makes lncRNAs an attractive target for the treatment of cancer and can also be used as a marker for the diagnosis and prognosis of diseases due to their differential expression in diseased samples. This review delves into the correlation of the lncRNA transcriptome with the fundamental cellular signalling and how this crosstalk shapes the complexity of the oncogenic microhabitat.